Strategi Penentuan Harga Jasa Pendidikan - Yanti Fatmariyanti; Abdul Muin Bahaf; Anis Zohriah (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
Setting prices is a crucial step in ensuring the operational viability of a learning institution. The price of educational services will inevitably be impacted by the current boom in the education sector, which is marked by offers of numerous programs and more facilities. The purpose of this study is to learn more about how much educational services cost. Using books, journals, and other literature as well as reading sources and references from the internet, a qualitative research methodology was employed (library research). The research's findings led to the conclusion that pricing strategies for educational services can be based on value (value-based pricing), competition (competition-based pricing), or cost (cost-based pricing).